Morphological Characterization of Spiral Arms in Disk Galaxies from the IllustrisTNG50 Simulation and their Relation to the Properties of their Host Dark Matter Halos (2025)
We investigate the link between spiral structure and dark-matter halo properties in disk galaxies from the IllustrisTNG50 (ΛCDM) simulation. Disks were selected with kinematic filters; gas and stars were isolated, the mean density profile was computed, and the techniques of Barros Ramírez (2020) were adapted to characterize the spiral arms. An automated algorithm in polar coordinates, combining density-based clustering and graph theory, located arms defined as overdensities in the gas mass, and then quantified their width, length, and pitch angle. We show that these methods effectively identify spirals in isolated disks. We find that arm width increases with galactocentric radius, with a tracer-dependent gradient (gas is more sensitive). The pitch angle correlates positively with the galaxy’s mass components and negatively with subhalo concentration, suggesting that spiral geometry responds to the mass distribution and to the assembly history. Taken together, these results support the transient nature of spiral patterns and disk–halo coevolution, and represent a first step toward obtaining metrics that are comparable between simulations and observations. [Tomado de la introducción]